Resilience and its relationship with quality of life and comorbid substance use disorder in patients with type I bipolar disorder - Shady Mohamed Moustafa; Magda Taha Kamal Aldin; Haydy Hassan Sayed; Ahmed Elarabi Hendi (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Bipolar disorders (BD) are common psychiatric disorders. Stressful life events as well as comorbid Substance use disorders contribute to functional impairment in patients with BD. This study aimed to assess resilience and its relation to quality of life and severity of comorbid substance use disorders in patients with type I bipolar disorder. Sixty six type I bipolar disorder patients—currently in remission—were categorized into two groups: a group including 33 patients were compared to a sociodemographically matched group of 33 patients of similar disease related clinical variables with comorbid substance use disorder. Resilience, quality of life and severity of addiction were assessed for both groups. Results Resilience level was found to be significantly lower in bipolar with comorbid substance use group compared to bipolar group. Quality of life of bipolar patients with comorbid substance use was not only significantly impaired but also positively correlated to resilience level. There was a strong negative correlation between resilience level and all aspects of addiction severity in patients with type I bipolar disorder. Conclusion Level of resilience was found to be positively correlated to quality of life and negatively correlated to severity of comorbid substance use in patients with type I bipolar disorder.